The international law of the sea - Tanaka, Yoshifumi (Cambridge University Press, 2012)
The law of the sea is a complex and fascinating subject. This textbook explores the subject from the perspective of public international law, covering all the key topics from the legal regimes governing the different jurisdictional zones, to international co-operation for protection of the marine environment. Clarity of expression, engaging analysis and comprehensive coverage make this book essential reading for all students of the law of the sea.